Supporting students with the transition to university in a Covid world: expectations and reality - Sonia Hood; Edward Powell (Journal of Learning Development in Higher Education, 2022)
In the spring of 2021 concerns were being raised in the Teaching and Learning community at the University of Reading regarding the incoming cohort of students. With such disruption to their education would they be adequately prepared for university level study? What impact would this, in turn, have on support services, like Study Advice, and retention and progression rates? And what of our returning students? Are they adequately prepared for the academic challenges they will face at the next level of study? As a result, a University wide working group was established to research the issue and offer solutions to support students and staff with the 2021 transition of our new and returning students. This paper will report on the findings from focus groups with year 13 students and 6th form tutors, and questionnaire data gathered from our current students during the summer of 2021. It will highlight the perceived academic strengths and development areas from their various perspectives and their beliefs as to what issues they will face with transitioning to the next level. We will share our University response to this; how we supported students with their academic transition this academic year. Finally, we will report whether our predictions as to what students would present to Study Advice this year materialised; how we believe Covid will continue to affect students in the coming years; and how that in turn will affect demand levels and types of support we as a Learning Development service will offer.